The website profile utilization as a media for disseminating information on playgroup and kindergarten Si Jempol Kota Tarakan - Muhammad Fadlan; Hadriansa Hadriansa; Mussalimah Mussalimah (Universitas Muhammadiyah Magelang, 2022)
Playgroup and Kindergarten KB-TK Si Jempol is an educational institution that hopes to become a role model in early childhood education in Kalimantan Utara. However, there is fundamental problem faced by partner, namely partner do not have integrated school information media, so that it can lead to misinformation. This community service aims to overcome the problems faced by partner related to the challenges of the society 5.0 era, especially in Kalimantan Utara. In this program, the solutions are divided into two main parts, namely development and training on the use of partner profile websites. The service activities carried out synchronously where partner also plays a role in carrying out this activity well. There are three main stages in this program, including the preparation stage, the design stage, and the mentoring stage. The result of this program is a website profile that partner can use as an integrated information dissemination platform.